Structural rationalisation of co-crystals formed between trithiocyanuric acid and molecules containing hydrogen bonding functionality - Ahn, Sung-Hoon; PrakashaReddy, J.; Kariuki, B. M.; Chatterjee, S.; Ranganathan, A.; Pedireddi, V. R.; Rao, C. N. R.; Harris, Kenneth D. M. (Chemistry - A European Journal, 2005)
Crystallisation of trithiocyanuric acid (TTCA) from various organic solvents that have hydrogen bonding capability (acetone, 2-butanone, dimethylformamide, dimethyl sulfoxide, methanol and acetonitrile) leads to the formation of co-crystals in which the solvent molecules are incorporated together with TTCA in the crystal structure. Structure determination by single-crystal X-ray diffraction reveals that these co-crystals can be classified into different groups depending upon the topological arrangement of the TTCA molecules in the crystal structure. Thus, three different types of single-tape arrangements of TTCA molecules and one type of double-tape arrangement of TTCA molecules are identified. In all co-crystals, hydrogen-bonding interactions are formed through the involvement of N-H bonds of TTCA molecules in these tapes and the other molecule in the co-crystal. Detailed rationalisation of the structural properties of these co-crystals is presented.
Symposium on Chemistry-A European Conference - Stimulating Concepts in Chemistry, Inst Sci Ingenierie Supramoleculaires, Strasbourg, FRANCE, APR 15, 2005
Keywords: crystal engineering; hydrogen bonds; nitrogen heterocycles; structure elucidation

Metal-induced reductive ring opening of 1,2,4,5-tetrazines: Three resulting coordination alternatives, including the new non-innocent 1,2-diiminohydrazido(2-) bridging ligand system - Maji, Somnath; Sarkar, B.; Patra, S.; Fiedler, Jan; Mobin, Shaikh M.; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Inorganic Chemistry, 2006)
{Reaction of 3,6-diaryl-1,2,4,5-tetrazines (aryl = R = phenyl, 2-furyl or 2-thienyl) with 2 equiv of Ru(acac)(2)(CH3-CN)(2) results in reductive tetrazine ring opening to yield diruthenium complexes [
Keywords: crystal engineering; hydrogen bonds; molecular; recocynition; Self-assembly; supramolecular chemistry

Hydrolytic conversion of a metal-organic polyhedron into a metal-organic framework - Mallick, Arijit; Garai, Bikash; Diaz, David Diaz; Banerjee, Rahul (Angewandte Chemie-International Edition, 2013)
Keywords: cage compounds; crystal engineering; hydrophobic effect; metal-organic frameworks; Self-assembly

Acyl-transfer reactions in molecular crystals: reactivity correlation with crystal structure - Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: crystal engineering; intermolecular interactions; solid-state reactions

Design and synthesis of 3D porous diamondoid frameworks by cocrystallization - Tothadi, Srinu; Little, Marc A.; Hasell, Tom; Briggs, Michel E.; Chong, Samantha Y.; Cooper, Andrew I. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: cocrystals; crystal engineering; Porous Organic Cages

Pharmaceutical solids in crystal engineering - Nangia, Ashwini (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: cocrystals; crystal engineering; Supramolecular synthon

Structural diversity in serine derived homochiral metal organic frameworks - Kundu, Tanay; Banerjee, Rahul (Journal of Chemical Sciences, 2014)
Two new Zn(II) and Cd(II) based homochiral metal-organic frameworks (MOFs) [SerCdOAc and Zn(Ser)(2)] have been synthesized using pyridyl functionalized amino acid, viz., serine, as an organic linker. The SerCdOAc structure is three dimensional, while that of the Zn(Ser)(2) is two dimensional. The polar voids of the corresponding MOFs are filled with solvent molecules (water in the case of SerCdOAc and methanol in the case of Zn(Ser)(2)). In both cases, metal centres, i.e., Zn(II) and Cd(II), are hexacoordinated. However, with a change in the solvent for synthesis, ligand coordination mode and incorporation of additional coordinated anion resulted in a great change in the final MOF architecture. Herein, for the first time, we could achieve structural variety and synthesize MOFs composed of only metal ion and pyridyl functionalized amino acid linker.
Keywords: Amino acid; crystal engineering; hydrogen bonding; metal organic framework

Drug-drug molecular salt hydrate of an anticancer drug gefitinib and a loop diuretic drug furosemide: an alternative for multidrug treatment - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Patwadkar, Manjusha V.; Badiger, Manohar V.; Gonnade, Rajesh G. (Journal of Pharmaceutical Sciences, 2015)
A 1:1 monohydrate salt containing gefitinib, an orally administrated chemotherapy treatment for lung and breast cancers and furosemide, a loop diuretic drug, commonly used in the treatment of hypertension and edema, has been prepared. The molecular salt crystallized in triclinic P-1 space group. The CO bond lengths (similar to 1.26 angstrom) in the COOH group show that proton transfer has occurred from furosemide to morpholine moiety of the gefitinib suggesting cocrystal to be ionic. The morpholine moiety of the gefitinib showed significant conformational change because of its involvement in conformation dictating the strong N-H center dot center dot center dot O hydrogen bonding interaction. The strong hydrogen bonding interaction between gefitinib and furosemide places their benzene rings in stacking mode to facilitate the generation of pi-stack dimers. The neighboring dimers are bridged to each other via water molecule through N-H center dot center dot center dot O, C-H center dot center dot center dot O, O-H center dot center dot center dot N, and O-H center dot center dot center dot O interactions. The remarkable stability of the salt hydrate could be attributed to the strong hydrogen bonding interactions in the crystal structure. Interestingly, release of water from the lattice at 140 degrees C produced new anhydrous salt that has better solubility and dissolution rate than salt hydrate. The drug-drug molecular salt may have some bearing on the treatment of patient suffering from anticancer and hypertension. (C) 2015 Wiley Periodicals, Inc. and the American Pharmacists Association
Keywords: cancer chemotherapy; cocrystals; crystal engineering; crystal structure; dissolution rate; hydrate; phase transition; solubility; stability; thermal analysis

Intramolecular cyclization of carbonate and thiocarbonate derivatives of myo-inositol in the solid state: implications for acyl group transfer reactions in molecular crystals - Tamboli, Majid I.; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Krishnaswamy, Shobhana (Chemistry-A European Journal, 2015)
Racemic 4-O-phenoxycarbonyl and 4-O-phenoxythiocarbonyl derivatives of myo-inositol orthoformate undergo thermal intramolecular cyclization in the solid state to yield the corresponding 4,6-bridged carbonates and thiocarbonates, respectively. The thermal cyclization also occurs in the solution and molten states, but less efficiently, suggesting that these cyclization reactions are aided by molecular pre-organization, although not strictly topochemically controlled. Crystal structures of two carbonates and a thiocarbonate clearly revealed that the relative orientation of the electrophile and the nucleophile in the crystal lattice facilitates the intramolecular cyclization reaction and forbids the intermolecular reaction. The correlation observed between the chemical reactivity and the non-covalent interactions in the crystal of the reactants provides a way to estimate the chemical stability of analogous molecules in the solid state.
Keywords: crystal engineering; cyclitols; inositols; nucleophilic substitution; solid-phase synthesis

Mechanochemical synthesis of N-salicylideneaniline: thermosalient effect of polymorphic crystals - Mittapalli, Sudhir; Perumalla, D. Sravanakumar; Nangia, Ashwini (IUCRJ, 2017)
Polymorphs of the dichloro derivative of N-salicylideneaniline exhibit mechanical responses such as jumping (Forms I and III) and exploding (Form II) in its three polymorphs. The molecules are connected via the amide N-H center dot center dot center dot O dimer synthon and C-Cl center dot center dot center dot O halogen bond in the three crystal structures. A fourth high-temperature Form IV was confirmed by variable-temperature single-crystal X-ray diffraction at 180 degrees C. The behaviour of jumping exhibited by the polymorphic crystals of Forms I and III is due to the layered sheet morphology and the transmission of thermal stress in a single direction, compared with the corrugated sheet structure of Form II such that heat dissipation is more isotropic causing blasting. The role of weak C-Cl center dot center dot center dot O interactions in the thermal response of molecular crystals is discussed.
Keywords: crystal design; crystal engineering; Halogen bonding; hydrogen bonding; intermolecular interactions; materials science; mechanochemistry; polymorphism

Crystal engineering: an outlook for the future - Nangia, Ashwini K.; Desiraju, Gautam R. (Angewandte Chemie-International Edition, 2019)
Crystal Engineering has traditionally dealt with molecular crystals. It is the understanding of intermolecular interactions in the context of crystal packing and in the utilization of such understanding in the design of new solids with desired physical and chemical properties. We outline here five areas which come under the umbrella of Crystal Engineering and where we feel that a proper planning of research efforts could lead to higher dividends for science together with greater returns for humankind. We touch on themes and domains where science funding and translation efforts could be directed in the current climate of a society that increasingly expects applications and utility products from science and technology. The five topics are: 1)pharmaceutical solids; 2)industrial solid state reactions; 3)mechanical properties with practical applications; 4)MOFs and COFs framework solids; 5)new materials for solar energy harvesting and advanced polymers.
Keywords: crystal engineering; metal-organic frameworks; pharmaceutical solids; solar energy; solid-state reactions

Supramolecular synthon hierarchy in sulfonamide cocrystals with syn-amides and N-oxides - Bolla, Geetha; Nangia, Ashwini (IUCRJ, 2019)
Sulfonamide drugs are well known antibacterial and antimicrobial molecules for pharmaceutical development. Building a library of suitable supramolecular synthons for the sulfonamide functional group and understanding their crystal structures with partner coformer molecules continues to be a challenge in crystal engineering. Although a few sulfonamide cocrystals with amides and N-oxides have been reported, the body of work on sulfonamide synthons is limited compared with those that have carboxylic acids and carboxamides. To address this structural gap, the present work is primarily focused on sulfonamide-lactam and sulfonamide-syn-amide synthons with drugs such as celecoxib, hydrochlorothiazide and furosemide. Furthermore, the electrostatic potential of previously reported cocrystals has been recalculated to show that the negative electrostatic potential on the lactam and syn-amide O atom is higher compared with the charge on carboxamide and pyridine N-oxide O atoms. The potential of sulfonamide molecules to form cocrystals with syn-amides and lactams are evaluated in terms of the electrostatic potential energy for the designed supramolecular synthons.
Keywords: cocrystals; crystal engineering; sulfonamides; supramolecular synthons; syn-amides

Photo-induced cracking in a Bi-component molecular solid: capturing structural intermediates - Ahsan, Mollah Rohan; Mishra, Manish Kumar; Mukherjee, Arijit (Chemistry-An Asian Journal, 2025)
A photo-responsive bi-component solid is designed based on robust large synthons. The study not only provides a template-based approach for a system that was difficult to photo-dimerize, but the designed solid also leads to photo-induced cracking upon photodimerization. The delicate structural design helps in capturing the structural intermediates, which reveals a possible reorientation of the photodimer within the crystal to maintain structural integrity.
Keywords: bi-component solid; crystal engineering; photoinduced cracking; single-crystal-to-single crystal transformation; [2+2] photodimerization

From brittle to elastic: substituent effects on mechanical flexibility in aromatic amide crystals - Bhowmik, Aritra; Das, Nirmal; Saxena, Ashish Kumar; Mishra, Kamini; Barsu, Nagaraju; Mishra, Manish Kumar (Chemistry-An Asian Journal, 2026)
Mechanical flexibility in molecular crystalline materials represents a compelling paradigm shift from the long-held perception of crystals as inherently brittle solids. Herein, we demonstrate a brittle-to-elastic transition by subtle molecular modification in a pair of structurally analogous aromatic amides; N-[(4-methoxyphenyl)methyl]formamide (N4MFA, Crystal 1) and N-benzylformamide (NBFA, Crystal 2). Despite their close structural similarity, Crystal 1 exhibits brittle fracture under minimal stress, whereas Crystal 2 shows 1D elastic flexibility with reversible bending. Structural, computational, and mechanical analyses reveal that this contrast arises from substituent-controlled supramolecular packing. In Crystal 1, the methoxy (-OCH3) group promotes dense, anisotropic packing, leading to rigidity and fracture under stress. Removing the substituent in Crystal 2 enhances isotropy, pi-pi stacking, and interlocked packing, enabling reversible strain during elastic bending. Nanoindentation, energy framework, and elastic tensor analyses confirm this transition: Crystal 2 shows near-isotropic stiffness (E max/E min = 1.65) and interconnected energy networks, whereas Crystal 1 exhibits pronounced anisotropy (E max/E min = 3.95) and 1D cohesion. Hirshfeld surface analysis supports more balanced contacts in the elastic crystal. This work establishes a direct structure-mechanical correlation, showing that minor chemical modifications can tune flexibility and provide insights to guide the development of adaptive crystalline materials.
Keywords: crystal engineering; Elasticity; Mechanical property; nanoindentation; responsive crystals